Designing an English for Accountant Syllabus for Indonesian Tertiary Students - Yuniastari, Rintya; da Silva, Anna Marietta (Cetta: Jurnal Ilmu Pendidikan, 2025)
One of the fields of expertise that have rapidly advanced in the process of creating economic and financial decisions and regulations locally, nationally, and globally is accounting. This field necessitates not only high accounting knowledge and skills but also communication skills in english, which still holds a status of the world’s lingua franca. Hence, the need for an english for occupational purposes, particularly the English for accountants. This study attempts to investigate the needs of the accounting students as well as professionals and propose a syllabus to meet the needs. To realize the former, job-reporting and interview to two professional accountants were administered, as well as survey to fifty accounting students. To realize the later, the needs analysis results were analyzed and priorities were made. The needs analysis demonstrates that learning speaking skills and listening skills in the context of accounting should be prioritized over the reading and writing skills. More emphasis should also be given to the formal style of communication as well as exposures to actual accounting-related terminologies.  All of which has become the basis for proposing a syllabus design that integrates theme, task, and genre under the principles of Content-Based Instruction that centers on the teaching the subject content through language. Therefore, the syllabus should be prepared not only by the English instructor but also the accounting instructor. Such a syllabus is expected to provide a learning experience that mirrors the actual demand and context of a professional accountant, including the actual and contextual english language usage.